2001
DOI: 10.1046/j.1570-7458.2001.00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the parasitization capacity of Trichogramma cordubensis influenced by the age of the females?

Abstract: We investigated the parasitization capacity of Trichogramma cordubensis Vargas & Cabello (Hymenoptera: Trichogrammatidae) females aged 24 h, 48 h, 72 h, 96 h, 120 h, and 144 h, using Ephestia kuehniella Zeller (Lepidoptera: Pyralidae) eggs as hosts. Wasps were held without hosts during the period of ageing, therefore being increasingly time‐limited with respect to parasitization as they got older. The total number of parasitized hosts decreased as the age of the parasitoid increased. However, the proportion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…However, whatever the tested group of females, we found that oviposition was more important during the first 48 h of females' life time, especially for T. oleae (line 2F). This seems to be in total accordance with Ventura Garcia et al (2001) who perceived that the number of eggs laid by Trichogramma species as well as all pro-ovigenic wasps in the first 24 h takes an important place in their total fecundity, regardless of the age of the females. Nevertheless, life expectancy is strongly temperature dependent.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, whatever the tested group of females, we found that oviposition was more important during the first 48 h of females' life time, especially for T. oleae (line 2F). This seems to be in total accordance with Ventura Garcia et al (2001) who perceived that the number of eggs laid by Trichogramma species as well as all pro-ovigenic wasps in the first 24 h takes an important place in their total fecundity, regardless of the age of the females. Nevertheless, life expectancy is strongly temperature dependent.…”
Section: Discussionsupporting
confidence: 89%
“…Ventura Garcia, Wajnberg, Melo Oliveira, and Tavares (2001) reported that female Trichogramma with the lowest longevity are also those with the lowest parasitization capacity. However, our results showed that at almost all temperatures, Trichogramma oleae (line 2F) females displayed the highest cumulative mean fertility, despite its short longevity and oviposition period, in comparison with T. oleae (line 2) and Trichogramma cacoeciae (strain D).…”
Section: Discussionmentioning
confidence: 99%
“…We assumed that TO females deprived from A. pernyi host for such a long period of time (i.e., more than 4 days) resulted in intensive oosorption and consequently the parasitization ability of TO females decreased. The variation in multiparasitism rates in our results did confirm that parasitism ability of TO on A. pernyi host was largely age dependent (Fleury and Bouletreau 1993;Godfray 1994;Garcia et al 2001;Makee 2005;Huang et al 2017).…”
Section: Trichogramma Ostriniae Age Impacts On Multiparasitismsupporting
confidence: 79%
“…The average fecundity increased as temperatures rose from 15°C to 32°C, after which it declined at higher temperatures. According to Garcia et al (2001), the adverse effect of high temperatures on fecundity may be attributed to a reduction in female longevity. However, even at high temperatures of 35°C and 37°C, T. bourarachae continued to parasitize a substantial number of eggs, with rates of 53.41 and 36.20 eggs per female, respectively.…”
Section: Discussionmentioning
confidence: 99%